Chemical constituent from roots of morinda citrifolia using polar solvent (chloroform) / Siti Farahin Akma Hazani - Hazani, Siti Farahin Akma (Faculty of Applied Sciences, 2019)
Experiment was conducted on root of Morinda citrifolia which belongs to the family Rubiaceae found throughout in the tropical region of the entire world. This genus of species contain varies of medical benefit such as anti-cancer, antimicrobial and anti inflammatory. The objectives set up for this M. citrifolia is to extract and isolate compounds from the roots of M. citrifolia by using chloroform, meanwhile for the second one is to identify and elucidate the structure of the compounds by using spectroscopic methods. Works on the chloroform extract of the roots of M. citrifolia through a series of column chromatography have resulted on isolation of two anthraquinone namely as nordamnacanthal and rubiadin. All of these structures were established by spectroscopic analysis which included 10 NMR, MS techniques and comparing with previous data.